Reassessing the health impacts of trade and investment agreements: a systematic review of quantitative studies, 2016–20. Issue 5 (May 2022) - Barlow, Pepita; Sanap, Rujuta; Garde, Amandine; Winters, L Alan; Mabhala, Mzwandile A; Thow, Anne-Marie
Summary: To ensure a high level of health protection, governments must ensure that health and trade policy objectives are aligned. We conducted a systematic review of the health impacts of trade policies, including trade and investment agreements (TIAs), to provide a timely overview of this field. We systematically reviewed studies evaluating the health impacts of trade policies published between Jan 19, 2016, and July 10, 2020. Included studies were quantitative studies evaluating the impact of TIAs and trade policies on health determinants or outcomes. We evaluated methodological quality and performed a narrative synthesis. 21 of 28 067 articles identified via searches met our criteria. Methodologically strong studies found reduced child mortality, deteriorating worker health, rising supplies of sugar, ultra-processed food, tobacco, and alcohol supplies, and increased drug overdoses following trade reforms, compared with the time periods before trade reform. However, associations varied substantially across contexts and socioeconomic characteristics. Our findings show that trade policies, including TIAs, have diverse effects on health and health determinants. These effects vary substantially across contexts and socioeconomic groups. Governments seeking to adopt healthy trade policies should consider these updated findings to ensure that opportunities for health improvement are leveraged and widely shared, while harms are avoided, especially among vulnerable groups.